High-precision forming process for edge pressing film of silk screen plate
Through the high-precision molding process, the cleaning of the screen printed screen and the forming of the edge film are automatically completed, solving the problem of low manual bonding accuracy in the existing technology, and achieving high-precision finished products and performance improvements.
Patent Information
- Application Number
- CN202411712693.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing screen printed screen edge press film is artificially bonded, resulting in poor accuracy, consumes a lot of labor, affecting the quality of the finished product and increasing costs.
Using high-precision molding technology, the cleaning of the screen printed screen and the forming of the edge-pressing film are automatically completed by preparing the PI film and using ultrasonic cleaning and laser marking equipment to improve accuracy and efficiency.
It realizes high-precision molding of the screen printed edge film, with an accuracy of up to 20μm, saving labor, improving process efficiency, and enhancing the stain removal, anti-fog, self-cleaning and photocatalytic properties of the edge film.
Smart Images

Figure BDA0005156155100000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of edge pressing films, and in particular to a high-precision molding process for an edge pressing film of a silk-screen screen. Background Art
[0002] The screen printing stencil is composed of stainless steel mesh of different mesh sizes and latex coated on the mesh mounted on a mesh frame. The latex is removed from the openings of the stencil pattern design. When the scraper passes over the stencil, the slurry applied to the stencil can be printed on the substrate through the openings of the pattern group. The main factor that determines the printing thickness is the thickness of the latex.
[0003] After the silk screen printing stencil is prepared, it needs to be attached with a film to ensure the accuracy of the silk screen printing stencil. However, the existing silk screen printing stencil edge pressing film is manually attached, which requires a lot of manpower and has poor accuracy and cannot guarantee the quality of the finished silk screen printing stencil, resulting in a certain impact on the overall cost. Summary of the invention
[0004] The main purpose of the present invention is to provide a high-precision molding process for a screen printing stencil edge pressing film, which can effectively solve the problems in the background technology.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A high-precision molding process for a screen printing stencil edge pressing film includes the following steps:
[0007] S1: Prepare molding materials: butyl titanate, anhydrous ethanol, diethanolamine, hydrochloric acid, methyl orange, and distilled water;
[0008] S2: Prepare the equipment for preparation: beaker, stirring rod, stainless steel container, ultrasonic generator, spin coater, oven, laser scribing equipment;
[0009] S3: Preparation of PI film: diethanolamine is selected as a hydrolysis inhibitor, butyl titanate is used as a titanium source, and anhydrous ethanol is used as a solvent. 10-20 parts of butyl titanate, 3-5 parts of diethanolamine, 50-60 parts of anhydrous ethanol, and an appropriate amount of deionized water are taken respectively. First, 3 / 5 of the total amount of anhydrous ethanol is added to a beaker, and butyl titanate and diethanolamine are slowly added to the anhydrous ethanol under continuous stirring. After stirring for 1 hour, a mixed solution A is obtained. Deionized water, the remaining 2 / 5 of the total amount of anhydrous ethanol and 0.1-0.3 parts of ferric nitrate are mixed evenly to form a solution B. Solution B is dripped dropwise into solution A under continuous stirring, and stirring is continued for 1 hour. All reaction processes are carried out at room temperature to complete the preparation of the PI film;
[0010] S4: Cleaning of the screen printing stencil: prepare acetone and ethanol, use ultrasonic cleaning to clean the screen printing stencil until the larger dust and oil stains are removed, place the screen printing stencil in a stainless steel container with deionized water, and perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 10 minutes, then use ethanol to perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 15 minutes, rinse the screen printing stencil with deionized water after the ultrasonic cleaning is completed, and finally use hot air to blow the screen printing stencil dry and set aside for use;
[0011] S5: Attachment treatment: Attach the PI film to the silk screen stencil, heat the attached silk screen stencil at 80°C for 10 minutes, take it out, place the silk screen stencil with PI film in room temperature air for natural drying, so as to complete the heat application of the PI film, use laser scribing equipment to cut the silk screen stencil with PI film until it is cut into a suitable shape, remove the excess PI film, so as to complete the molding process of the silk screen stencil edge film.
[0012] Preferably, in step S3, 15 parts of butyl titanate, 3 parts of diethanolamine, 50 parts of anhydrous ethanol, and 20 parts of deionized water are used.
[0013] Preferably, in step S3, 20 parts of butyl titanate, 5 parts of diethanolamine, 60 parts of anhydrous ethanol, and 30 parts of deionized water are used.
[0014] Preferably, in step S3, 10 parts of butyl titanate, 4 parts of diethanolamine, 55 parts of anhydrous ethanol, and 25 parts of deionized water are used.
[0015] Preferably, in step S2, a transducer is installed at the bottom of the stainless steel container.
[0016] Preferably, in step S1, the molecular weight of butyl titanate is 340.35, and its properties are analytically pure ≥98%, the molecular weight of anhydrous ethanol is 46.07, and its properties are analytically pure ≥99.7%; the molecular weight of diethanolamine is 105.14, and its properties are analytically pure ≥98%; the molecular weight of hydrochloric acid is 36.46, and its properties are 36-38% HCL; the molecular weight of methyl orange is 327.33, and its properties are analytically pure ≥98%; the molecular weight of distilled water is 18.02, and its properties are double distilled.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The edge pressing film prepared by the present invention not only has the performance of removing organic matter, but also has relatively good anti-fog performance, and also shows relatively good self-cleaning performance. At the same time, the edge pressing film also has good photocatalytic and hydrophilic properties. At the same time, the common processing technology for the edge pressing film mostly uses a cutter to cut it into a suitable shape, and then manually attaches the edge pressing film to the silk screen. This process has low efficiency and its accuracy is 0.2mm. The molding time of each silk screen is relatively long. The process method of the present invention can be automatically completed by equipment, and can save labor while its accuracy can reach 20μm. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention relates to a high-precision forming process of a screen printing stencil edge pressing film, comprising the following operating steps:
[0021] S1: Prepare molding materials: butyl titanate, anhydrous ethanol, diethanolamine, hydrochloric acid, methyl orange, distilled water, wherein the molecular weight of butyl titanate is 340.35, and the properties are analytically pure ≥98%, the molecular weight of anhydrous ethanol is 46.07, and the properties are analytically pure ≥99.7%; the molecular weight of diethanolamine is 105.14, and the properties are analytically pure ≥98%; the molecular weight of hydrochloric acid is 36.46, and the properties are HCL36-38%; the molecular weight of methyl orange is 327.33, and the properties are analytically pure ≥98%; the molecular weight of distilled water is 18.02, and the properties are double distilled;
[0022] 15 parts of butyl titanate, 3 parts of diethanolamine, 50 parts of anhydrous ethanol, and 20 parts of deionized water;
[0023] 20 parts of butyl titanate, 5 parts of diethanolamine, 60 parts of anhydrous ethanol, and 30 parts of deionized water;
[0024] 10 parts of butyl titanate, 4 parts of diethanolamine, 55 parts of anhydrous ethanol, and 25 parts of deionized water;
[0025] S2: Prepare the equipment for preparation: beaker, stirring rod, stainless steel container, ultrasonic generator, spin coater, oven, laser scribing equipment, and a transducer is installed at the bottom of the stainless steel container;
[0026] S3: Preparation of PI film: diethanolamine is selected as a hydrolysis inhibitor, butyl titanate is used as a titanium source, and anhydrous ethanol is used as a solvent. 10-20 parts of butyl titanate, 3-5 parts of diethanolamine, 50-60 parts of anhydrous ethanol, and an appropriate amount of deionized water are taken respectively. First, 3 / 5 of the total amount of anhydrous ethanol is added to a beaker, and butyl titanate and diethanolamine are slowly added to the anhydrous ethanol under continuous stirring. After stirring for 1 hour, a mixed solution A is obtained. Deionized water, the remaining 2 / 5 of the total amount of anhydrous ethanol and 0.1-0.3 parts of ferric nitrate are mixed evenly to form a solution B. Solution B is dripped dropwise into solution A under continuous stirring, and stirring is continued for 1 hour. All reaction processes are carried out at room temperature to complete the preparation of the PI film;
[0027] S4: Cleaning of the screen printing stencil: prepare acetone and ethanol, use ultrasonic cleaning to clean the screen printing stencil until the larger dust and oil stains are removed, place the screen printing stencil in a stainless steel container with deionized water, and perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 10 minutes, then use ethanol to perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 15 minutes, rinse the screen printing stencil with deionized water after the ultrasonic cleaning is completed, and finally use hot air to blow the screen printing stencil dry and set aside for use;
[0028] S5: Attachment treatment: Attach the PI film to the silk screen stencil, heat the attached silk screen stencil at 80°C for 10 minutes, take it out, place the silk screen stencil with PI film in room temperature air for natural drying, so as to complete the heat application of the PI film, use laser scribing equipment to cut the silk screen stencil with PI film until it is cut into a suitable shape, remove the excess PI film, so as to complete the molding process of the silk screen stencil edge film. Specific embodiment one:
[0030] A high-precision molding process for a screen printing stencil edge pressing film includes the following steps:
[0031] S1: Prepare molding materials: butyl titanate, anhydrous ethanol, diethanolamine, hydrochloric acid, methyl orange, distilled water, including 15 parts of butyl titanate, 3 parts of diethanolamine, 50 parts of anhydrous ethanol, and 20 parts of deionized water, wherein the molecular weight of butyl titanate is 340.35, and the properties are analytically pure ≥98%, the molecular weight of anhydrous ethanol is 46.07, and the properties are analytically pure ≥99.7%; the molecular weight of diethanolamine is 105.14, and the properties are analytically pure ≥98%; the molecular weight of hydrochloric acid is 36.46, and the properties are HCL36-38%; the molecular weight of methyl orange is 327.33, and the properties are analytically pure ≥98%; the molecular weight of distilled water is 18.02, and the properties are double distilled;
[0032] S2: Prepare the equipment for preparation: beaker, stirring rod, stainless steel container, ultrasonic generator, spin coater, oven, laser scribing equipment, and a transducer is installed at the bottom of the stainless steel container;
[0033] S3: Preparation of PI film: diethanolamine is selected as a hydrolysis inhibitor, butyl titanate is used as a titanium source, and anhydrous ethanol is used as a solvent. 10-20 parts of butyl titanate, 3-5 parts of diethanolamine, 50-60 parts of anhydrous ethanol, and an appropriate amount of deionized water are taken respectively. First, 3 / 5 of the total amount of anhydrous ethanol is added to a beaker, and butyl titanate and diethanolamine are slowly added to the anhydrous ethanol under continuous stirring. After stirring for 1 hour, a mixed solution A is obtained. Deionized water, the remaining 2 / 5 of the total amount of anhydrous ethanol and 0.1-0.3 parts of ferric nitrate are mixed evenly to form a solution B. Solution B is dripped dropwise into solution A under continuous stirring, and stirring is continued for 1 hour. All reaction processes are carried out at room temperature to complete the preparation of the PI film;
[0034] S4: Cleaning of the screen printing stencil: prepare acetone and ethanol, use ultrasonic cleaning to clean the screen printing stencil until the larger dust and oil stains are removed, place the screen printing stencil in a stainless steel container with deionized water, and perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 10 minutes, then use ethanol to perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 15 minutes, rinse the screen printing stencil with deionized water after the ultrasonic cleaning is completed, and finally use hot air to blow the screen printing stencil dry and set aside for use;
[0035] S5: Attachment treatment: Attach the PI film to the silk screen stencil, heat the attached silk screen stencil at 80°C for 10 minutes, take it out, place the silk screen stencil with PI film in room temperature air for natural drying, so as to complete the heat application of the PI film, use laser scribing equipment to cut the silk screen stencil with PI film until it is cut into a suitable shape, remove the excess PI film, so as to complete the molding process of the silk screen stencil edge film. Specific embodiment 2:
[0037] A high-precision molding process for a screen printing stencil edge pressing film includes the following steps:
[0038] S1: Prepare molding materials: butyl titanate, anhydrous ethanol, diethanolamine, hydrochloric acid, methyl orange, distilled water, including 20 parts of butyl titanate, 5 parts of diethanolamine, 60 parts of anhydrous ethanol, and 30 parts of deionized water, wherein the molecular weight of butyl titanate is 340.35, and the properties are analytically pure ≥98%, the molecular weight of anhydrous ethanol is 46.07, and the properties are analytically pure ≥99.7%; the molecular weight of diethanolamine is 105.14, and the properties are analytically pure ≥98%; the molecular weight of hydrochloric acid is 36.46, and the properties are HCL36-38%; the molecular weight of methyl orange is 327.33, and the properties are analytically pure ≥98%; the molecular weight of distilled water is 18.02, and the properties are double distilled;
[0039] S2: Prepare the equipment for preparation: beaker, stirring rod, stainless steel container, ultrasonic generator, spin coater, oven, laser scribing equipment, and a transducer is installed at the bottom of the stainless steel container;
[0040] S3: Preparation of PI film: diethanolamine is selected as a hydrolysis inhibitor, butyl titanate is used as a titanium source, and anhydrous ethanol is used as a solvent. 10-20 parts of butyl titanate, 3-5 parts of diethanolamine, 50-60 parts of anhydrous ethanol, and an appropriate amount of deionized water are taken respectively. First, 3 / 5 of the total amount of anhydrous ethanol is added to a beaker, and butyl titanate and diethanolamine are slowly added to the anhydrous ethanol under continuous stirring. After stirring for 1 hour, a mixed solution A is obtained. Deionized water, the remaining 2 / 5 of the total amount of anhydrous ethanol and 0.1-0.3 parts of ferric nitrate are mixed evenly to form a solution B. Solution B is dripped dropwise into solution A under continuous stirring, and stirring is continued for 1 hour. All reaction processes are carried out at room temperature to complete the preparation of the PI film;
[0041] S4: Cleaning of the screen printing stencil: prepare acetone and ethanol, use ultrasonic cleaning to clean the screen printing stencil until the larger dust and oil stains are removed, place the screen printing stencil in a stainless steel container with deionized water, and perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 10 minutes, then use ethanol to perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 15 minutes, rinse the screen printing stencil with deionized water after the ultrasonic cleaning is completed, and finally use hot air to blow the screen printing stencil dry and set aside for use;
[0042] S5: Attachment treatment: Attach the PI film to the silk screen stencil, heat the attached silk screen stencil at 80°C for 10 minutes, take it out, place the silk screen stencil with PI film in room temperature air for natural drying, so as to complete the heat application of the PI film, use laser scribing equipment to cut the silk screen stencil with PI film until it is cut into a suitable shape, remove the excess PI film, so as to complete the molding process of the silk screen stencil edge film. Specific embodiment three:
[0044] A high-precision molding process for a screen printing stencil edge pressing film includes the following steps:
[0045] S1: Prepare molding materials: butyl titanate, anhydrous ethanol, diethanolamine, hydrochloric acid, methyl orange, distilled water, including 10 parts of butyl titanate, 4 parts of diethanolamine, 55 parts of anhydrous ethanol, and 25 parts of deionized water, wherein the molecular weight of butyl titanate is 340.35, and the properties are analytically pure ≥98%, the molecular weight of anhydrous ethanol is 46.07, and the properties are analytically pure ≥99.7%; the molecular weight of diethanolamine is 105.14, and the properties are analytically pure ≥98%; the molecular weight of hydrochloric acid is 36.46, and the properties are HCL36-38%; the molecular weight of methyl orange is 327.33, and the properties are analytically pure ≥98%; the molecular weight of distilled water is 18.02, and the properties are double distilled;
[0046] S2: Prepare the equipment for preparation: beaker, stirring rod, stainless steel container, ultrasonic generator, spin coater, oven, laser scribing equipment, and a transducer is installed at the bottom of the stainless steel container;
[0047] S3: Preparation of PI film: diethanolamine is selected as a hydrolysis inhibitor, butyl titanate is used as a titanium source, and anhydrous ethanol is used as a solvent. 10-20 parts of butyl titanate, 3-5 parts of diethanolamine, 50-60 parts of anhydrous ethanol, and an appropriate amount of deionized water are taken respectively. First, 3 / 5 of the total amount of anhydrous ethanol is added to a beaker, and butyl titanate and diethanolamine are slowly added to the anhydrous ethanol under continuous stirring. After stirring for 1 hour, a mixed solution A is obtained. Deionized water, the remaining 2 / 5 of the total amount of anhydrous ethanol and 0.1-0.3 parts of ferric nitrate are mixed evenly to form a solution B. Solution B is dripped dropwise into solution A under continuous stirring, and stirring is continued for 1 hour. All reaction processes are carried out at room temperature to complete the preparation of the PI film;
[0048] S4: Cleaning of the screen printing stencil: prepare acetone and ethanol, use ultrasonic cleaning to clean the screen printing stencil until the larger dust and oil stains are removed, place the screen printing stencil in a stainless steel container with deionized water, and perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 10 minutes, then use ethanol to perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 15 minutes, rinse the screen printing stencil with deionized water after the ultrasonic cleaning is completed, and finally use hot air to blow the screen printing stencil dry and set aside for use;
[0049] S5: Attachment treatment: Attach the PI film to the silk screen stencil, heat the attached silk screen stencil at 80°C for 10 minutes, take it out, place the silk screen stencil with PI film in room temperature air for natural drying, so as to complete the heat application of the PI film, use laser scribing equipment to cut the silk screen stencil with PI film until it is cut into a suitable shape, remove the excess PI film, so as to complete the molding process of the silk screen stencil edge film.
[0050] The performance of the edge-pressed film prepared according to the present invention is compared with the common edge-pressed film on the market, wherein specific embodiments 1 to 3 are recorded as embodiments 1-3, and the edge-pressed film on the market is recorded as a comparative example. The following is a comparison table:
[0051]
[0052] This shows that the edge-pressed film prepared by this method has better performance.
[0053] The edge pressing film prepared by the present invention not only has the performance of removing organic matter, but also has relatively good anti-fog performance, and also shows relatively good self-cleaning performance. At the same time, the edge pressing film also has good photocatalytic and hydrophilic properties. At the same time, the common processing technology for the edge pressing film mostly uses a cutter to cut it into a suitable shape, and then manually attaches the edge pressing film to the silk screen. This process has low efficiency and its accuracy is 0.2mm. The molding time of each silk screen is relatively long. The process method of the present invention can be automatically completed by equipment, and can save labor while its accuracy can reach 20μm.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-precision molding process for a screen printing stencil edge film, characterized in that: The steps include: S1: Prepare molding materials: butyl titanate, anhydrous ethanol, diethanolamine, hydrochloric acid, methyl orange, and distilled water; S2: Prepare the equipment for preparation: beaker, stirring rod, stainless steel container, ultrasonic generator, spin coater, oven, laser scribing equipment; S3: Preparation of PI film: diethanolamine is selected as a hydrolysis inhibitor, butyl titanate is used as a titanium source, and anhydrous ethanol is used as a solvent. 10-20 parts of butyl titanate, 3-5 parts of diethanolamine, 50-60 parts of anhydrous ethanol, and an appropriate amount of deionized water are taken respectively. First, 3 / 5 of the total amount of anhydrous ethanol is added to a beaker, and butyl titanate and diethanolamine are slowly added to the anhydrous ethanol under continuous stirring. After stirring for 1 hour, a mixed solution A is obtained. Deionized water, the remaining 2 / 5 of the total amount of anhydrous ethanol and 0.1-0.3 parts of ferric nitrate are mixed evenly to form a solution B. Solution B is dripped dropwise into solution A under continuous stirring, and stirring is continued for 1 hour. All reaction processes are carried out at room temperature to complete the preparation of the PI film; S4: Cleaning of the screen printing stencil: prepare acetone and ethanol, use ultrasonic cleaning to clean the screen printing stencil until the larger dust and oil stains are removed, place the screen printing stencil in a stainless steel container with deionized water, and perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 10 minutes, then use ethanol to perform ultrasonic cleaning on the screen printing stencil at a frequency of 20-40kHz for 15 minutes, rinse the screen printing stencil with deionized water after the ultrasonic cleaning is completed, and finally use hot air to blow the screen printing stencil dry and set aside for use; S5: Attachment treatment: Attach the PI film to the silk screen stencil, heat the attached silk screen stencil at 80°C for 10 minutes, take it out, place the silk screen stencil with PI film in room temperature air for natural drying, so as to complete the heat application of the PI film, use laser scribing equipment to cut the silk screen stencil with PI film until it is cut into a suitable shape, remove the excess PI film, so as to complete the molding process of the silk screen stencil edge film.
2. The high-precision molding process of the screen printing stencil edge film according to claim 1, characterized in that: In the step S3, 15 parts of butyl titanate, 3 parts of diethanolamine, 50 parts of anhydrous ethanol, and 20 parts of deionized water are prepared.
3. The high-precision molding process of the screen printing stencil edge film according to claim 1, characterized in that: In the step S3, 20 parts of butyl titanate, 5 parts of diethanolamine, 60 parts of anhydrous ethanol, and 30 parts of deionized water are added.
4. The high-precision molding process of the screen printing stencil edge film according to claim 1, characterized in that: In the step S3, 10 parts of butyl titanate, 4 parts of diethanolamine, 55 parts of anhydrous ethanol, and 25 parts of deionized water are added.
5. The high-precision molding process of the screen printing stencil edge film according to claim 1, characterized in that: In step S2, a transducer is installed at the bottom of the stainless steel container.
6. The high-precision molding process of the screen printing stencil edge film according to claim 1, characterized in that: In the step S1, the molecular weight of butyl titanate is 340.35, and its properties are analytically pure ≥98%, the molecular weight of anhydrous ethanol is 46.07, and its properties are analytically pure ≥99.7%; the molecular weight of diethanolamine is 105.14, and its properties are analytically pure ≥98%; the molecular weight of hydrochloric acid is 36.46, and its properties are 36-38% HCL; the molecular weight of methyl orange is 327.33, and its properties are analytically pure ≥98%; the molecular weight of distilled water is 18.02, and its properties are double distilled.
Citation Information
Patent Citations
Method for preparing negative ion material used for organic pollutant and sewage treatment and having photo-catalysis performance
CN102895972A
TiO2-based photocatalytic self-cleaning glass and preparation method thereof
CN105293949A
Fe-doped TiO2 / diatomite composite photocatalyst as well as preparation method and application thereof
CN111298792A
Polyimide solar net plate and preparing method thereof
CN111605300A
Preparation method of hydrophobic solar cell screen printing plate
CN115923315A